Physiological upper limits of ventricular cavity size in highly trained adolescent athletes. Issue 4 (16th March 2005) - Makan, J; Sharma, S; Firoozi, S; Whyte, G; Jackson, P G; McKenna, W J
Abstract : Objectives: To define physiological upper limits of left ventricular (LV) cavity size in trained adolescent athletes. Design: Cross sectional echocardiographic study. Setting: British national sports training grounds and Olympic Medical Institute. Subjects: 900 elite adolescent athletes (77% boys) aged 15.7 (1.2) years participating in ball, racket, and endurance sports and 250 healthy controls matched for age, sex, and size. Main outcome measures: LV end diastolic cavity size. Results: Compared with controls, athletes had a larger LV cavity (50.8 (3.7) v 47.9 (3.5) mm), a difference of 6%. The LV cavity was > 54 mm in 18% athletes, whereas none of the controls had an LV cavity > 54 mm. The LV cavity exceeded predicted sizes in 117 (13%) athletes. Among the athletes with LV dilatation, 78% were boys, LV size ranged from 52–60 mm, and left atrial diameter and LV wall thickness were enlarged. Systolic and diastolic function were normal. None of the athletes in the study had an LV cavity size > 60 mm. LV cavity size correlated with age, sex, heart rate, and body surface area. Conclusion: Highly trained junior athletes usually have only modest increases in LV cavity size. A proportion of trained adolescent athletes have LV cavity size exceeding predicted values but, in absolute terms, LV cavity rarely exceeds 60 mm as in patients with dilated cardiomyopathy. In highly trained adolescent athletes with an LV cavity size > 60 mm and any impairment of systolic or diastolic function, the diagnosis of dilated cardiomyopathy should be considered.